Kewajiban Notaris Membacakan Akta Autentik Bagi Penghadap Disabilitas Rungu - Sihombing, Adam Jose; Adipramartha, Gede Wahyu (Universitas Semarang, 2024)
The purpose of this article is to analyze the regulations on the Notary's obligations in reading an authentic deed for a client or hearing person who is deaf, based on the regulations in force in Indonesia. In addition, this research was conducted to find out and examine the legal formulation regarding the obligation to read authentic documents that are relevant to the situation of clients or speakers who are deaf. Remembering Law No. 2 of 2014 concerning amendments to Law No. 30 of 2004 concerning the position of notaries and the legal formulation regarding the obligation to read authentic deeds relating to the situation of deaf disabled persons Normative legal research is carried out by examining various formal legal rules, such as laws, regulations, and literature containing theoretical concepts that are related to problems. The results of this study show that in the regulations regarding the obligation of notaries to read authentic deeds for deaf persons in the Notary Position Law in Indonesia, there is still a vacuum in norms and only regulates the reading of deeds intended for non-disabled persons or normal persons only. The Law on Notary Positions in Indonesia was amended to include provisions regarding sign language interpreters for deaf people, provided they have passed the sign language interpreter qualification exam held by the Professional Certification Institute established by a professional organization or university. This legal formulation answers the obligation to read authentic documents that are relevant to the situation of deaf people in the future. Tujuan artikel ini ialah menganalisis pengaturan kewajiban Notaris dalam halnya membacakan suatu akta autentik bagi klien atau penghadap yang mengalami disabilitas rungu jika dilandasi oleh peraturan yang berlaku di Indonesia. Ditambah lagi, penelitian ini diteliti untuk mengetahui dan mengkaji formulasi hukum terkait kewajiban membacakan akta autentik yang relevan dengan keadaan klien atau penghadap yang mengalami disabilitas rungu. Mengingat UU No. 2 Tahun 2014 tentang Perubahan Atas UU No.30 Tahun 2004 mengenai Kedudukan Notaris dan rumusan hukum mengenai kewajiban membacakan akta autentik yang berkaitan dengan keadaan penyandang disabilitas tunarungu. Penelitian hukum normatif yang pelaksanaannya dengan dilakukannya pengkajian berbagai aturan hukum yang bersifat formal seperti undang-undang, peraturan-peraturan serta literatur yang berisi konsep teoritis yang dihubungkan dengan permasalahanHasil dari kajian ini memperlihatkan kalau dalam pengaturan perihal kewajiban Notaris membacakan akta autentik bagi penghadap disabilitas rungu dalam UU Jabatan Notaris di Indonesia masih ada kekosongan norma dan hanya mengatur perihal pembacaan akta yang ditujukan bagi penghadap non disabilitas atau Penghadap normal saja. UU Jabatan Notaris di Indonesia diubah sehingga mencakup ketentuan mengenai juru bahasa isyarat bagi penyandang tuna rungu, dengan syarat telah lulus ujian kualifikasi juru bahasa isyarat yang diselenggarakan oleh Lembaga Sertifikasi Profesi yang didirikan oleh organisasi profesi atau perguruan tinggi. Rumusan hukum ini menjawab tentang kewajiban membacakan akta autentik yang relevan dengan keadaan penyandang tuna rungu di kemudian hari.